2010
DOI: 10.1371/journal.pone.0015787
|View full text |Cite
|
Sign up to set email alerts
|

Surface Expressed Nucleolin Is Constantly Induced in Tumor Cells to Mediate Calcium-Dependent Ligand Internalization

Abstract: BackgroundNucleolin is one of the major proteins of the nucleolus, but it is also expressed on the cell surface where is serves as a binding protein for variety of ligands implicated in tumorigenesis and angiogenesis. Emerging evidence suggests that the cell-surface expressed nucleolin is a strategic target for an effective and nontoxic cancer therapy.Methodology/Principal FindingsBy monitoring the expression of nucleolin mRNA, and by measuring the level of nucleolin protein recovered from the surface and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
160
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(169 citation statements)
references
References 80 publications
(172 reference statements)
9
160
0
Order By: Relevance
“…This result appears consistent with our previous reports that gelonin is quite stable in fusions due to its structure [26,32] , which consequently contributes to the retention of its activity even after fusion with F3 peptide. To elucidate any anti-cancer targeting effects of F3-Gel or gelonin alone, for the in vitro cell experiments, we used HeLa, LnCaP, 9L, and U87 MG cancer cells because these cell lines were fully examined in other previous studies related to the F3 peptide [18,33] . In contrast to the equipotent intrinsic activity compared with unmodified gelonin in the cell-free conditions (Figure 2), in the U87 MG cell lines, F3-Gel exhibited a significantly greater ability to reduce the protein level to less than 50% than that of the gelonin ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result appears consistent with our previous reports that gelonin is quite stable in fusions due to its structure [26,32] , which consequently contributes to the retention of its activity even after fusion with F3 peptide. To elucidate any anti-cancer targeting effects of F3-Gel or gelonin alone, for the in vitro cell experiments, we used HeLa, LnCaP, 9L, and U87 MG cancer cells because these cell lines were fully examined in other previous studies related to the F3 peptide [18,33] . In contrast to the equipotent intrinsic activity compared with unmodified gelonin in the cell-free conditions (Figure 2), in the U87 MG cell lines, F3-Gel exhibited a significantly greater ability to reduce the protein level to less than 50% than that of the gelonin ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the issues related to the short half-life and intrinsic toxicity at high doses of F3-Gel, further studies are underway to develop a nanoparticle-based drug delivery system to extend the plasma half-life and increase the tumor targeting efficiency at the lower dose. Based on reports that the interaction between nucleolin-targeted ligands and nucleolin is influenced by the isoelectric point [33,35] , it would be helpful to devise appropriate delivery vehicles for the F3-Gel by optimizing the physicochemical properties, such as surface charge, in the presence of F3 peptide to enable an efficient and safe therapeutic effect of F3-Gel.…”
Section: Discussionmentioning
confidence: 99%
“…Post-transcriptionally, NCL binding to mRNAs may effect expression of particular proteins, with NCL binding to the p53 mRNA 5'UTR resulting in translational activation, while its binding to gadd45α mRNA in response to arsenite treatment and K294-SUMOylation blocks the degradation of this transcript (Takagi et al 2005;Zhang et al 2015). Remarkably, NCL has even been reported to be constitutively displayed on the cell surface, where it may act as a ligand for particular growth-regulatory ligands and viruses (Fujiki et al 2014;Hovanessian et al 2010;Nisole et al 2002).…”
Section: Ncl Throughout the Cell -Nucleolus Nucleoplasm Cytoplasm Amentioning
confidence: 99%
“…tion (18), arsenite (28,47,48,69), and inflammatory cytokines (70). Our previous findings showed that GADD45␣ was one of the crucial mediators of arsenite-induced apoptosis (47,48).…”
mentioning
confidence: 95%